(untitled) - Silvestri, Linda Anne (Philadelphia, Pa.,London, 2002)
This popular book/CD-ROM review package is designed to provide students with a total of 3,500 NCLEX-RN practice questions in a truly unique format. Chapters in the book are organized according to the client needs categories and the integrated concepts and processes identified in the latest NCLEX-RN test plan. It features practice questions, answers, and detailed rationales on the same page to provide immediate feedback on students' responses. Rationales for both correct and incorrect responses, along with test-taking strategies, help students learn from their mistakes and develop an effective approach to the exam. Each chapter also contains new critical thinking/free-text entry questions that allow students to practice fundamental skills needed to pass the new NCLEX-RN exam such as prioritizing and decision-making. The CD-ROM contains all 1,800 multiple-choice and free-text entry questions from the book, plus 1,700 additional practice questions for an even more complete review.
Keywords: Practical nursing,Thực hành điều dưỡng; Examinations, questions, etc.,Thi, câu hỏi, v.v